Ultrasonography of the Kidney: A Pictorial Review - Kristoffer Lindskov Hansen; Michael Bachmann Nielsen; Caroline Ewertsen (Diagnostics, 2015)
Ultrasonography of the kidneys is essential in the diagnosis and management of kidney-related diseases. The kidneys are easily examined, and most pathological changes in the kidneys are distinguishable with ultrasound. In this pictorial review, the most common findings in renal ultrasound are highlighted.